2004
DOI: 10.1007/s11664-004-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and failure behavior of Ta-Ni nanostructured/amorphous diffusion barriers for copper metallization

Abstract: This work examines the thin-film properties and diffusion barrier behavior of sputtered Ta-Ni films, aiming at depositing highly crystallization-resistant and conductive diffusion barriers for Cu metallization. Structural analysis indicates that the as-deposited Ta-Ni films indeed have a glassy structure and are free from highly resistive intermetallic compounds. Examining Si/Ta-Ni/Cu stacked samples reveals that thermally induced failure of amorphous Ta-Ni barriers is triggered by the barrier's reaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Only Cu diffraction peaks were detected when the stacked films were annealed at or below 500°C. Interestingly, the intensity of the Cu (111) diffraction peak substantially exceeded that obtained in an earlier study, 13 implying that the Cu film had a strong (111) texture when copper was deposited onto the Si/Ta 0.25 Ni 0.75 substrate. The strong Cu (111) texture may result from the high Ni content in Ta 0.25 Ni 0.75 , which easily provides a face-centeredcubic closely packed structure after annealing.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Only Cu diffraction peaks were detected when the stacked films were annealed at or below 500°C. Interestingly, the intensity of the Cu (111) diffraction peak substantially exceeded that obtained in an earlier study, 13 implying that the Cu film had a strong (111) texture when copper was deposited onto the Si/Ta 0.25 Ni 0.75 substrate. The strong Cu (111) texture may result from the high Ni content in Ta 0.25 Ni 0.75 , which easily provides a face-centeredcubic closely packed structure after annealing.…”
Section: Resultsmentioning
confidence: 55%
“…The diffraction spectra revealed that the as-deposited Ta-Ni thin film indeed had an amorphous structure (not shown). 13 In addition, the microstructure of Ta 0.75 Ni 0.25 thin film remained amorphous at an elevated temperature of 750°C for 5 min, as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 87%
“…13 Our previous study has also shown that electron-gun-evaporated Ta-Co and sputtered Ta-Ni thin films indeed have an amorphous structure, and are free from intermetallic compounds up to 500°C and 700°C. 14 A superior barrier characteristic for evaporated Ta-Co and sputtered Ta-Ni thin films in preventing Cu diffusion can also be found up to annealing temperatures of 500°C and 700°C. Thin-film crystallization and Ta-Co and Ta-Fe thin films have not yet been reported.…”
Section: Introductionmentioning
confidence: 94%
“…The resistivity for as-deposited films showed the same level with that of our previous study on sputtered Si/Ta-Ni film. 14 The films were subsequently annealed at an elevated temperature to evaluate the variation in resistivity dependence of annealing temperature. The tiny variation in resistivity of the film was found (range 140-165 ⍀-cm) at an annealing temperature range from 300°C to 700°C for the Si/ Ta 0.5 Fe 0.5 film, as shown in Fig.…”
Section: Crystallization Characteristics Of Deposited Filmsmentioning
confidence: 99%
“…6,7 Crystalline Ta and TaN thin films are the most promising diffusion barriers for preventing the highly diffusive copper from the penetrating the barrier to react with silicon. [8][9][10][11] Sputter-deposited TaN is most commonly used as the diffusion barrier, owing to its good thermal stability at a high temperature and limited solid solubility in Cu.…”
Section: Introductionmentioning
confidence: 99%